First records of xylophilous Basidiomycetes (Fungi) in Mondaí, Santa Catarina (Southern Brazil) - Marisa de Campos Santana; Clarice Loguercio-Leite (Biotemas)
A taxonomic survey of xylophilous Basidiomycetes resulted in the identification of 21 species belongingto the families Boreostereaceae Jülich (1), Ganodermataceae Donk (2), Hymenochaetaceae Imazeki & Toki (6), Me- ripilaceae Jülich (2), Podoscyphaceae Reid (1), Polyporaceae Fr.: Corda (8) and Schizophyllaceae Quél. (1). All species are new records for Mondaí.